Wole Soyinka. Het profiel van een Nobelprijswinnaar - Vermeulen, Julien (Afrika Focus, 1987)
It is always difficult to define exactly why a particular author has been awarded the Nobel Prize for Literature. This approach will deal with four different aspects which may have contributed to Wole Soyinka's. award. It cannot be denied that Soyinka is the author of an extensive and richly varied work, which has been appreciated by critics the world over. Especially the satirical qualities of his style have been praised on many occasions. But we have to focus our attention on two other important aspects. We can only achieve a full understanding of Soyinka's dramas when we interpret them against the background of Yoruba drama and Yoruba cultural tradition. And we can only appreciate Soyinka's work if we pay attention to the social context in which it is situated. This political commitment, as well as the international reputation Soyinka has helped to create as a director and an actor, are essential elements that have contributed to this Nobel Prize award. KEYWORDS : African literature in English, Nobel Prize, Wole Soyinka